Development of Mobile Application for a Sizing and Cost Analysis of Grid-Connected Photovoltaic System - Ahmad, Nurul Izzati; Mohamad Nor, Ahmad Fateh (Evolution in Electrical and Electronic Engineering, 2022)
Usually, power is generated using fossil fuels and heat, which pollute the atmosphere by emitting CO2 (CO2). When fossil fuels are burned, carbon dioxide and other greenhouse gases are released into the atmosphere, causing global warming and climate change. Photovoltaic (PV) systems provide solar energy that is independent of the sun or the surroundings. However, due to Malaysia's tropical environments, where heavy rains and dry days occur annually due to the tropical rainy season, this sort of PV system has several issues. An ON-grid solar system linked to the grid ensures that electricity is always delivered to the user's infrastructure. Solar energy systems also need a high initial investment. Using a mobile application may help alleviate this difficulty. A mobile application for sizing and cost analysis of grid- connected PV systems is being developed to help users estimate the size and cost of a grid-connected PV system. This software may help consumers since it is available on Google Play or Appstore. This mobile application can calculate total load consumption, photovoltaic size, total energy production, tariff calculations, cost, and payback period. These mobile applications must be compared to computing methodologies to measure their efficacy and durability. So, computational method methodology is developed for grid-connected PV system size and cost analysis. According to the results of this mobile app, the monthly load usage is 615.42 kWh, the cost is RM 6460, and the total monthly bill after PV installation is 187.48. The monthly savings after installing PV system is RM 52.51. The app's final result displays a total payback period of 10.3 years. This implies that by comparing the findings of the mobile app and the computational approach, the mobile app can appropriately compute load consumption, PV sizing, tariff calculation, pricing, and total payback time.